(untitled) (Journal of the College of Basic Education, 2023)
The teaching methods used at the present time are of a throwaway nature in most subjects, especially geography, as this method has become useless and incompatible with the modern educational trend, due to determining its impact on the development of the student’s ability, whose role in it becomes negative.The researcher felt, through her experience in the field of teaching, that the curricula for social subjects are subject to memorization and memorization of information in the first place, and they do not help the development of mental skills.Also, the traditional method used in teaching measures the student’s ability to retrieve and remember information, and this contradicts the philosophical view of modern education, which stresses the necessity of developing students’ mental skills.Many students and some teachers of social subjects believe that the issue of constancy and retention of scientific knowledge is a difficult issue, and in the researcher’s belief that this weakness is due to many reasons, foremost of which are traditional teaching methods without working to stimulate thinking or develop the student’s ability to research and investigate, so such thinking is necessary To understand and assimilate information and facts, and the student is active and interacting with the educational situation.Hence, it has become imperative for the teacher to look for the appropriate teaching aids through which he moves away from the old methods that make the learner a receiver and his role is specific and based on listening and receiving information only.Among the other important problems that have emerged in the educational field is the huge amount of information, especially the study of geography, which raised complaints about the extent of the rigidity of the material and the difficulty of understanding and assimilating it.The researcher touched this weakness, as she noticed some students memorize information and facts without understanding or realizing the relationships between them. The use of concepts as elements to organize the curricula, so it is necessary to carry out an experimental study in which the existing weakness is addressed in an attempt to find a solution to it.